(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The work is devoted to the study of scale insects of pests - fruit plants, their species composition, distribution, food connections in the conditions of the Fergana Valley. The article presents research materials on the biological characteristics of the violet scale insect.